The Effect of Audit Quality, Company Size, and Liquidity on Going Concern Audit Opinion in Indonesian Manufacturing Companies - Afrisca, Resya Nazella; Surifah, Surifah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of audit quality, company size, and liquidity on going concern audit opinions (GCAO) in manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study employed a quantitative approach with secondary data obtained from financial statements and annual reports. The sample comprised manufacturing companies that were initially selected through random sampling. The resulting sample was then refined using purposive sampling based on predefined eligibility criteria. Hypothesis testing was conducted using logistic regression analysis with the assistance of SPSS. The dependent variable in this study was the going-concern audit opinion, while the independent variables consisted of audit quality, company size, and liquidity. The results indicate that audit quality has a significant negative effect on going concern audit opinions. Firm size has a significant positive effect on GCAO, while liquidity has no significant effect on GCAO. This study provides empirical evidence that audit quality functions as an effective monitoring mechanism in reducing the likelihood of GCAO. Large firms are not necessarily protected from receiving such opinions, while liquidity is not a determining factor of GCAO.